Hubungan antara Perilaku Hidup Bersih dan Sehat (PHBS) Tatanan Rumah Tangga dengan Kejadian Diare pada Balita - Laila Jamil; Retno Mardhiati; Nurul Huriah Astuti (UHAMKA Press, 2019)
ABSTRACT Diarrhea is a public health problem, especially in infants. Diarrhea can be prevented if the community have a good implement Clean and Healthy Behavior (PHBS). This study aims to determine The Relationship Between Clean And Healthy Behavior (PHBS) Of The Household Part With The Incidence Of Childhood Diarrhea. Subjects in this study were the mother In The Working Area Of Puskesmas Mangunjaya Tambun Selatan Bekasi who have children aged 12- 59 months. The research design used is analytic survey research with cross sectional approach, data taken from respondent by using questionnaire. The analysis used for this reseach is univariate, bivariate, and multivariate. The results of univariate analysis in this study where most respondents didnt experience diarrhea occurence in infants in the last three months (62%), PHBS household arrangement (71,3%), have children 25-59 months old (73,1%), have male toddler (50,9%), ≥ 26 years old (80,6%), had recent high education (63,9%), has a family income month < UMR (68,5%), and has 1 toddler (80,6%). The results of bivariate test showed that there is a significant relationship between the behavior of clean and healthly live (PHBS) of the household order with the incidence of diarrhea in infacts In The Working Area Of Puskesmas Mangunjaya Tambun Selatan Bekasi 2018 (Pvalue 0,000). Puskesmas officers must be intensive and continuous in providing health counseling about the factors related to the incidence of chilhood diarrhe, especially Clean And Healthy Behavior (PHBS) Of The Household Part to community In The Working Area Of Puskesmas Mangunjaya Tambun Selatan Bekasi. Keyword : The Relationship Between Clean And Healthy Behavior, Childhood Diarrhea